Analisis Golongan Metabolit Sekunder Ekstrak Etanol Kulit Batang Cemara Laut (Casuarina equisetifolia L.) dan Cemara Gunung (Casuarina junghuhniana Mig.) - Ike G. Siregar; Daniel Lantang; Linus Y. Chrystomo (Jurnal Biologi Papua, 2022)
The use of medicinal plants as natural medicine is increasingly trend and developing rapidly to prevent and treat disease, also maintain human health. Spruce plants belong to Casuarinaceae family and Magnoliophyta, generally contain of secondary metabolite compounds such as: alkaloid, saponin, polyphenol, flavonoid, and tannin that can be efficacious to cure diseases in human. The purpose of this study was to analyze the secondary metabolites compound of Casuarina equisetifolia L. and Casuarina junghuhniana Mig. using the Fransworth phytochemical screening method of bark ethanol extracts. The analysis of phytochemical screening of spruce bark shows flavonoid, saponin and tannin activity, while the montain spruce shows alkaloid, steroid, saponin and tannin activity. Further research is needed to investigate the ethnopharmaceutical information on the use of the spruce plants as a traditional medicine.Key words: Spruce plants; screening; extract; analysis; phytochemical; secondary metabolite